Review of Pedagogy, Politics and Philosophy of Peace: Interrogating Peace and Peacemaking - Archer, Tim (In Factis Pax: Journal of Peace Education and Social Justice, 2017)
Book Review Pedagogy, Politics and Philosophy of Peace: Interrogating Peace and Peacemaking, edited by Carmen Borg & Michael Grech, Bloomsbury, 2017, 256 pp.